Evening primrose oil ameliorates tissue architecture, apoptosis, and oxidative stress in the pancreas of diabetic rats: Possible role of miR-21 - Ali Louei Monfared; Ali Menatnia (Iranian Journal of Basic Medical Sciences)
Objective(s): Activating apoptosis and oxidative stress contributes to the pathogenesis of diabetes. Evening primrose oil (EPO) has been shown to regulate lipid profiles and hyperglycemia under metabolic conditions. This study aimed to examine the effect of EPO on miR-21 expression, oxidative stress, apoptosis, and histological changes in the pancreas of male rats with experimental diabetes induced by streptozotocin (STZ).Materials and Methods: Thirty-two Wistar rats were divided into four distinct groups: control, diabetic, diabetic + EPO, and EPO. EPO was administered orally at a dose of 500 mg/kg, and STZ was administered intraperitoneally at a dose of 35 mg/kg for 28 days. In the end, the effects of treatments were assessed by measuring expressions of miR-21 in the pancreas with real-time PCR, pancreatic histological and immunohistochemical changes examinations, and oxidative stress assessment.Results: In the diabetic group, miR-21 expression and the levels of caspase-3 and malondialdehyde (MDA) were increased compared to the control group, while insulin expression and superoxide dismutase activity (SOD) levels were decreased significantly. Treatment with EPO resulted in a reduction of miR-21 and caspase-3 expression, as well as MDA levels, and an increase in insulin expression and SOD levels compared to the diabetic group. Additionally, supplementation with EPO demonstrated the ability to restore pancreatic tissue features, serum insulin levels, and blood glucose fluctuations.Conclusion: Collectively, the protective impacts of EPO in diabetic rats may be linked to the inhibition of miR-21/caspase-3/oxidative stress pathway, leading to the restoration of pancreatic β-cell function and structure.